2011
DOI: 10.1111/j.1439-0272.2011.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Do ureteral catheterisation procedures affect sexual functions? A controlled prospective study

Abstract: The use of ureteral stents is a common procedure in urology practice. We investigated whether the use of double-J stent had an effect on sexual functions or not. One hundred and seventy-seven cases were included in the study. Unilateral double-J stent was placed during ureteral stone treatment in one hundred and eight of these cases. Sixty-nine cases were included as the control group. 'International Index of Erectile Function' (IIEF) and 'Female Sexual Function Index' (FSFI) questionaries were assessed before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
1
19
0
1
Order By: Relevance
“…The so-called "stent-related symptoms" range from mild discomfort, dysuria, and hematuria, to more significant morbidities, such as UTI, reflux, mal-positioning, fracture, and encrustation [7]. In addition to all of these, a DJ stent is also known to have a significant impact on sexual function in both genders [14]. This aspect is rarely talked about, especially in certain cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The so-called "stent-related symptoms" range from mild discomfort, dysuria, and hematuria, to more significant morbidities, such as UTI, reflux, mal-positioning, fracture, and encrustation [7]. In addition to all of these, a DJ stent is also known to have a significant impact on sexual function in both genders [14]. This aspect is rarely talked about, especially in certain cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Non-stent procedures had no impact on general sexual function in both sexes even though one or two domains of the administered questionnaires were mildly impaired, including erectile function and orgasmic function in men and sexual desire in women. One study reported that sexual deterioration in women recovered 1 month after stent removal [19]. In another study, the IIEF score remained unchanged on the 10th day after stent removal when compared with the preoperative baseline value [16].…”
Section: Discussionmentioning
confidence: 99%
“…The study publication years ranged from 2007 to 2017. Studies were from three countries (one from Italy [15], one from Egypt [16] and three from Turkey [17][18][19]). All five studies were non-randomized controlled trials.…”
Section: Literature Searchmentioning
confidence: 99%
“…This questionnaire has 'sexual matters' as one of 6 domains. To the best of our (Bolat et al, 2017;Eryildirim et al, 2012;Sofer et al, 2012). The remaining two used the IIEF-5 questionnaire which is an abridged version consisting of only 5 questions (Mosharafa et al, 2016;Sighinolfi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%